Aplicación de recubrimientos a base de almidones y clavo de olor en aguacate Hass, Ecuador - Jimenez, Ronald (2024)
The avocado (Persea americana Mill), Hass variety has great commercial export potential due to its nutritional properties, poor postharvest agricultural practices in Ecuador accelerate the deterioration and decrease in the quality of this fruit, therefore economic losses, for which the application of coatings based on cassava (Manihot esculenta), taro (Colocasia esculenta) and Chinese potato (Colocasia esculenta Schott) starches, with essential oil of cloves (Syzygium aromaticum), the latter provides an antimicrobial effect, with this , it is intended to reduce the deterioration of the fruit. The tests carried out on Hass avocados were: soluble solids, pH and titratable acidity, weight loss, color in the epidermis and microbiological control; the same ones that were stored for 14 days at a temperature of 27°C and 79% relative humidity in the city of Santo Domingo-Ecuador. As results, it was determined that the coatings based on cassava starch with 0.06% essential oil of cloves presented the best characteristics; soluble solids of 6.13°Brix, pH of 6.50, titratable acidity with 0.09%, weight loss 0.65%, epidermis color: Luminosity (L*), Chroma (C) and Hue (°h) decrease at As the days go by, indicating that the avocado has reached consumption maturity, the microbiological count indicates a slowdown in the growth of molds and yeasts; Regarding the treatments with taro starch and Chinese potato (Eddo), there were no significant differences between their treatments and interactions with a 95.0% confidence level. The application of antimicrobial edible coatings is recommended as an optional procedure, since they do not alter the physical-chemical characteristics of the avocado.